Traffic Risk Image in The Light of the Road Situation Assessment Questionnaire - Krzysztof Horoszkiewicz; Ryszard Cibor; Bartosz Horoszkiewicz (Kazimierz Wielki University, 2023)
Introduction: Drivers often lack reflection on their behaviour. For predictive purposes and educational interventions, it is useful to know the individual traffic risk picture of the driver under investigation. Objective: This paper aimed to show the psychometric properties of the questionnaire and to establish a hierarchy of traffic situations in terms of perceptions of associated danger. Material and Methods: A total of 548 people aged between 18 and 68 years participated in the study. A self-administered questionnaire method was used to measure situational (road) awareness and the ability to anticipate the consequences of engaging in unsafe road traffic actions. The tool's accuracy was verified with the 'Controversy' questionnaire, which is used to measure the severity of drivers' normative beliefs about breaking traffic laws. Results: Satisfactory psychometric values of the questionnaire were obtained. After taking into account the correlation of measurement errors, an acceptable fit was obtained: χ2 /df = 2.48; GFI = 0.95; AGFI = 0.92; CFI = 0.96; RMSEA = 0.06 (0.048-0.072). Mean values and standard deviations for 14 descriptions of unsafe traffic situations were shown. Conclusions: The satisfactory reliability and accuracy of the measurement allow the method to be used in research and individual diagnosis in the areas of transport psychology and education. Overtaking at pedestrian crossings, on a bend, uphill, and continuing to drive despite fatigue are the most dangerous traffic situations associated with the risk of traffic accidents.